How memorable is halal tourism in Japan and the United Kingdom? - Hamid, Mamoona; Siew, Imm Ng; Ho, Jo Ann; Abd Rahman, Azmawani (Salento University Publishing, 2023)
The provision of halal products and services for Muslim tourists would be a competitive edge for tourism destinations as the Muslim population is increasing. This research examines halal-friendly attributes provided by non-Muslim country destinations (Japan and UK) and determines their roles in creating memorable tourism experiences and driving behavioral intentions. The questionnaire was collected from 349 Muslim tourists who have visited UK or Japan once in the last two years. Underpinned by Script theory and Stimulus-Organism-Response theory, the proposed structural model was found to adequately describe the variance in memorable tourism experience and behavioral intention of Muslim tourists; four attributes (halal food & beverages, enhancement of halal experiences, halal-friendly hotels, and halal-friendly social environment) were positively related to memorable tourism experience and recommend intention, and all five attributes including halal-friendly services information had a significant influence on revisit intention of Muslim tourists. In addition, a memorable tourism experience is a significant mediator linking four halal-friendly attributes (except halal-friendly services information) and behavioral intention.